Persepsi Mahasiswa Terhadap Aplikasi TikTok Sebagai Media Dakwah - Ashabul Kahpi; Emi Puspita Dewi (ScidacPlus, 2024)
The presence of social media such as Tik Tok makes the communication process easier and more effective. This is the case with da'wah activities. Da'wah must be in accordance with the concept of al-Islamu sholih likulli zaman wa makan (in accordance with the conditions of time and era). This research is entitled